Principles for managing in complexity - Proud, Emma (LearnAdapt, 2020)
Written by Toby Lowe and Shaheen Warren (Centre for Public Impact) and Sam Sharp (Overseas Development Institute), with input from Jamie…

Farewell DFID … a personal obituary - Mason, Phil (LinkedIn - Phil Mason, 2020)
Reflection on how DFID was created.

How to manage complexity: four lessons for DFID’s new Secretary of State - LearnAdapt (Medium, 2019)
Lessons for DFID in addressing complex problems without creating complicated, workload heavy programmes.

Adaptive programming - Vowles, Pete (DFID Bloggers, 2013)
Staff blogs from the UK Department for International Development. Get real-life perspectives from those on the ground to fight poverty and join in the debate.